Mathematical modeling of business process optimization in the context of digital transformation - Горбаченко, Станіслав Анатолійович; Горбаченко, С. А.; Horbachenko, Stanislav A.; Чепурна, Олена Євгенівна; Чепурна, О. Є.; Chepurna, Olena Ye. (Одеса : Фенікс, 2026)
In the context of digital transformation, the optimization of business processes requires a transition from descriptive approaches to rigorous mathematical models capable of integrating time, cost, technological, risk and institutional parameters into a single evaluation system. This approach creates the basis for more informed management decisions, makes it possible to formalize the choice of the trajectory of digital changes and provides an analytical basis for improving the efficiency of the enterprise in an unstable competitive environment
Horbachenko, S., Chepurna O. Mathematical modeling of business process optimization in the context of digital transformation. Соціально-політична та правова система України в цифрову епоху: сучасні виклики : матеріали Міжнар. наук.-практ. конф. (м. Одеса, 22 квіт. 2026 р.) : у 2-х т. / за заг. ред. С. Ківалова ; НУ «Одес. юрид. академія». Одеса : Фенікс, 2026. Т. 2. С. 522-525. URL: https://doi.org/10.32837/11300.33287
Keywords: математичне моделювання; бізнес-процеси; цифрова трансформація; оптимізація; цифровізація; конкурентоспроможність; mathematical modeling; business processes; digital transformation; optimization; digitalization; competitiveness